Formation and transformation of mineral phases in biomass ashes and evaluation of the feedstocks for application in high-temperature processes. (July 2023) - Reinmöller, Markus; Schreiner, Marcus; Laabs, Marcel; Scharm, Christoph; Yao, Zhitong; Guhl, Stefan; Neuroth, Manuela; Meyer, Bernd; Gräbner, Martin
Abstract: Biomasses are known for their variety of ash systems, often accompanied by limiting effects such as fouling, sintering, slagging, agglomeration and corrosion, which affect thermochemical conversion processes (combustion, gasification, pyrolysis etc.). To explore those limiting effects, five different feedstocks from agricultural, woody, and processed biomasses are investigated after ashing in a temperature range between 200 and 815 °C. The ash composition and their specific distribution inside the particles are studied using X-ray fluorescence (XRF) and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX). Distinct differences are detected in the ashes from various biomasses, indicating that the ash systems can be homogeneous (mainly authigenic origin) or heterogeneous (with significant contributions of detrital/technogenic origin). Using X-ray diffraction (XRD), the formation and transformation of mineral phases are monitored in the ashes produced at various temperatures. The data are then compared to the results of thermochemical calculations. The experimental findings agree almost completely with those calculated using the FactSage™ software package. In connection with the identified mineral phases, the release behavior of the main alkali species, potassium, is monitored as a function of the ashing temperature. Based on these results indicating the ashes' mineral phase composition and their observed heterogeneity, the high-temperature behavior of the ash fusion temperatures (AFT) and ash fusion interval (AFI) between deformation and flow temperature can be ascertained. Finally, based on their ashing behavior, the biomasses' potential use in thermochemical conversion processes at high temperatures is evaluated.